Stress and self-efficacy as specific predictors of safety at work in the aviation sector - Magdalena Ślazyk-Sobol (Nofer Institute of Occupational Medicine, 2021)
Background The article addresses the issue of attitudes towards safety at work in the context of subjective variables such as psychological stress and the subjective self-efficacy of workers in the aviation sector. The research was exploratory in nature. It focused on capturing the individual experiences of ground handling staff at Polish and Slovak airports. Among the 326 people surveyed were engineers, firefighters, mechanics and electricians – a crew that works in difficult and threatening working conditions on a daily basis, often experiencing unexpected accidents and breakdowns. The psychosocial factors in industry 4.0 and this branch of industry itself are – according to the authors – verified empirically quite poorly. Taking care of safety at work and strengthening a positive attitude towards safety seems to be a key aspect of management in such units.